Understanding human knowledge: Philosophical Essays - Stroud, Barry (Oxford Oxford university press, 2002)
Since the 1970s Barry Stroud has been one of the most original contributors to the philosophical study of human knowledge. This volume presents the best of Stroud's essays in this area. Throughout, he seeks to clearly identify the question that philosophical theories of knowledge are meant to answer, and the role scepticism plays in making sense of that question. In these seminal essays, he suggests that people pursuing epistemology need to concern themselves with whether philosophical scepticism is true or false. Stroud's discussion of these fundamental questions is essential reading for anyone whose work touches on the subject of human knowledge.